Comparative Management and Organization Theory: A Marriage Needed - Negandhi, Anant R. (Academy of Management Journal, 1975)
An avenue for integration between two seemingly related areas, namely, cross-cultural comparative management, and organization theory, is provided as a result of an examination of recent developments and changes in the organization theory discipline. It is argued that such integration will enrich research studies undertaken by scholars of different orientations.